Heterogeneous Exposure Associations in Observational Cohort Studies: The Example of Blood Pressure in Older Adults. Issue 1 (8th October 2019) - Odden, Michelle C; Rawlings, Andreea M; Khodadadi, Abtin; Fern, Xiaoli; Shlipak, Michael G; Bibbins-Domingo, Kirsten; Covinsky, Kenneth; Kanaya, Alka M; Lee, Anne; Haan, Mary N; Newman, Anne B; Psaty, Bruce M; et al.
Abstract: Heterogeneous exposure associations (HEAs) can be defined as differences in the association of an exposure with an outcome among subgroups that differ by a set of characteristics. In this article, we intend to foster discussion of HEAs in the epidemiologic literature and present a variant of the random forest algorithm that can be used to identify HEAs. We demonstrate the use of this algorithm in the setting of the association between systolic blood pressure and death in older adults. The training set included pooled data from the baseline examination of the Cardiovascular Health Study (1989–1993), the Health, Aging, and Body Composition Study (1997–1998), and the Sacramento Area Latino Study on Aging (1998–1999). The test set included data from the National Health and Nutrition Examination Survey (1999–2002). The hazard ratios ranged from 1.25 (95% confidence interval: 1.13, 1.37) per 10-mm Hg increase in systolic blood pressure among men aged ≤67 years with diastolic blood pressure greater than 80 mm Hg to 1.00 (95% confidence interval: 0.96, 1.03) among women with creatinine concentration ≤0.7 mg/dL and a history of hypertension. HEAs have the potential to improve our understanding of disease mechanisms in diverse populations and guide the design of randomized controlled trials to control exposures in heterogeneous populations.